Large-scale seabird community structure along oceanographic gradients in the Scotia Sea and northern Antarctic Peninsula - Ollus, Victoria Marja Sofia; Biuw, Martin; Lowther, Andrew; Fauchald, Per; Deehr Johannessen, John Elling; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C.; Oosthuizen, W. Chris; Lindstrøm, Ulf (Frontiers in Marine Science, 2023)
The Scotia Sea and Antarctic Peninsula are warming rapidly and changes in species distribution are expected. In predicting habitat shifts and considering appropriate management strategies for marine predators, a community-level understanding of how these predators are distributed is desirable. Acquiring such data, particularly in remote areas, is often problematic given the cost associated with the operation of research vessels. Here we use cruise vessels as sampling platforms to explore seabird distribution relative to habitat characteristics. Data on seabird at-sea distribution were collected using strip-transect counts throughout the Antarctic Peninsula and Scotia Sea in the austral summer of 2019-2020. Constrained correspondence analysis (CCA) and generalized additive models (GAM) were used to relate seabird community composition, density, and species richness to environmental covariates. Species assemblages differed between oceanographic areas, with sea surface temperature 2 This is a provisional file, not the final typeset article and distance to coast being the most important predictors of seabird distribution. Our results further revealed a geographic separation of distinct communities rather than hotspot regions in the study area in summer. These findings highlight the importance of large-scale environmental characteristics in shaping seabird community structure, presumably through underlying prey distribution and interspecific interactions. The present study contributes to the knowledge of seabird distribution and habitat use as well as the baseline for assessing the response of Antarctic seabird communities to climate warming. We argue that cruise vessels, when combined with structured research surveys, can provide a cost-effective additional tool for the monitoring of community and ecosystem level changes.